Peran manajemen risiko hukum dalam menjaga kredibilitas dan kepercayaan lembaga perbankan - Fitriah, Destiana Mahmudatul (Maliki Interdisciplinary Journal, 2026)
Banking institutions play a strategic role as a key foundation of the national economic system, where their sustainability is largely determined by the level of public trust. In their operations, banks are inherently exposed to various types of risks, including legal risks that can arise from non-compliance with regulations, weaknesses in contract formulation, legal disputes, and changes in laws and regulations. If not optimally managed, legal risks can result in financial losses, sanctions from regulators, and a decline in the institution’s reputation, ultimately impacting customer trust and the bank’s stability. This research aims to examine the role of legal risk management in maintaining credibility and trust in banking institutions. The study focuses on analyzing the applicable regulatory framework, the process of identifying and mitigating legal risks, and their application in good corporate governance practices. The method used is a literature review with a descriptive-analytical approach, drawing on various regulations, scientific journals, and banking industry reports. The results indicate that the systematic and structured implementation of legal risk management, supported by a strong compliance function and a positive legal culture within the organization, plays a crucial role in enhancing bank credibility and sustainably maintaining public trust.